P6.019 Preventing Mother to Child Transmission of HIV: Challenges to Implementing WHO Guidelines. (13th July 2013) - Plessis, E du; Shaw, S Y; Gichuhi, M; Kimani, J; Gelman, L; Lester, R; Avery, L S
Abstract : Background: In 2009 the WHO provided updated guidelines for prevention of mother to child transmission (PMTCT) of HIV. Although the guidelines are based on the best available evidence and have the potential to reduce transmission, challenges remain in implementation. Data from Kenya illustrated that other factors may complicate the implementation of these guidelines. Methods: HIV-positive, pregnant women were recruited from two maternity hospitals in Nairobi, Kenya. Information was collected from participants (505 women to date) with surveys at baseline as well as 48 hour follow up as part of a study on the use of mobile technology in PMTCT programmes. Questions included socioeconomic characteristics, history of current/previous pregnancies, knowledge of PMTCT and Nevirapine use. Results: At presentation the majority of women were between 21 and 28 weeks pregnant (51.7%) with only 11.7% under 20 weeks gestational age. Although 60.5% of the women reported disclosing their status to their partners immediately, a quarter had not disclosed or refrained from answering. At 48 hour follow up, more than half the women (56.7%) reported attending four or more antenatal visits. Of the women, 71% reported receiving Nevirapine during labour while 91.9% of infants reportedly received Nevirapine. No significant difference was found between hospitals. Conclusion: In our sample, a higher number of women had disclosed to their partners than previously suggested, but there were still a significant number of women who had not disclosed, reducing the chance of male involvement in counselling. Although over 70% of women reported receiving Nevirapine during labour, the high percentage of women who present for their first visit after 14 weeks suggests that the use of AZT, as stated in the guidelines, is not feasible. Almost half the women did not attend four antenatal visits, suggesting that other factors may need to be considered for effective PMTCT.